Six ways to get a grip on patient and family centered care during the undergraduate medical years - Baerg, Krista; Anderson, Tara; Thiessen, Heather (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Patient and family-centered care and patient engagement practices have strong evidence-based links with quality and safety for both patients and health care providers. Expectations for patient and family-centered care have advanced beyond hearing the patient perspective and taking patient wishes into account. A participatory approach including patients as partners in their care journey is expected, but attitudes toward patient and family-centered care remain barriers in practice. As health service organizations shift from a system-centered approach to a patient and family-centered care delivery model, black ice occurs. In this Black Ice article, we present some practical tips for medical educators to improve opportunities for medical students to develop knowledge, attitudes, and skills that support patient and family-centered care.